Effect of photo, hetero and mixotrophic conditions on the growth and composition of Anabaena variabilis: An Energy Nexus approach - Zahra Khoobkar (Elsevier, 2021)
In the present study, three conditions of photoautotrophic (Case 1), heterotrophic (Case 2), and mixotrophic (Case 3) on the microalgal growth, lipid accumulation, and content of chlorophyll a and phycocyanin pigment in Anabaena vaginicola ISC90 have been investigated. Results shown that the specific growth rate (µmax) of case 1 compared to cases 2 and 3, had an increase of 30% and 26%, respectively. Additionally, the productivity rate (P) of case 3 in comparison with cases 1 and 2 grew by 30% and 92%, sequentially. Lipid and chlorophyll a content in case 3 were found to be significantly higher than other cases at the end of cultivation time. Also, during the first week phycocyanin pigment content in case 2 reached a massive increase compared to other cultures. In spite of the low rate of growth parameters in heterotrophic condition, this culture was found to be a great potential for phycocyanin pigment content production. Also, three kinetic growth models (Logistic, Gompertz and Richards) were evaluated, among which Gompertz showed the best fit for all conditions.